M2 macrophages and regulatory T cells in lethal prostate cancer - Erlandsson, Ann; Carlsson, Jessica; Lundholm, Marie; Fält, Anna; Andersson, Sven‐Olof; Andrén, Ove; Davidsson, Sabina (The Prostate, 2019)
Background Prostate cancer (PCa) is one of the most frequently diagnosed cancers in the world. Emerging evidence suggests that inflammatory cells such as M2 macrophages and regulatory T cells (Tregs) can contribute to cancer progression by suppressing the anti‐tumor immune response. This study investigated the number of CD163‐positive M2 macrophages in PCa tissue. It also investigated the correlation and interaction of M2 macrophages and Tregs. Methods This nested case‐control study included subjects from a cohort of men diagnosed with PCa as an incidental finding during transurethral resection of the prostate. The cases were 225 men who died from PCa, and the controls were 367 men who survived more than 10 years after PCa diagnosis without disease progression. Infiltrating CD163‐positive M2 macrophages and FOXP3/CD4‐positive Tregs in PCa tissue were identified using immunohistochemistry. The correlation and interaction of M2 macrophages and Tregs were assessed using Spearman's rank‐order correlation and a likelihood test, respectively. Logistic regression was used to estimate odds ratios (ORs) for lethal PCa and macrophage counts. Results The number of M2 macrophages and Tregs showed a significant correlation (P < 0.001) but no interactions. The OR for lethal PCa was 1.93 (95%CI: 1.23‐3.03) for men with high numbers of M2 macrophages. Also for cases with uncertain outcome (GS categories 3 + 4 and 4 + 3) high numbers of M2 macrophages does predict a poorer prognosis. Conclusions Our data showed that men with high numbers of M2 macrophages in the prostate tumor environment had increased odds of dying of PCa. It is possible that M2 macrophages, together with other suppressor cells such as Tregs, promote an immunosuppressive environment.